Proper Vaccination Timing Against Newcastle Disease in Regard to Maternal Immunity - Zaid Yaseen Ibrahim, Hadeel Mohammed Fayyadh (Revista Electronica de Veterinaria, 2022)
Newcastle disease (ND) is an economically important viral illness because it causes large production losses in affected poultry farms. Biosecurity and vaccination are considered the main ways for controlling infection with newcastle disease virus (NDV). The success of the vaccination process in early days of age depends on several factors. One of those factors is the serum level of the maternal antibodies (MAb). Our study was conducted to measure the MAb in Iraqi commercial poultry as a method of determining the proper age for first vaccination. Our data resulted in a mean age for proper vaccination of 11.1±0.88 day. The results were disperse and the proper vaccination age ranged from 4.8 to 22.8 days. For this reason, we recommend performing serologic test for MAb to properly design vaccination programs.